Antiulcer activity of 2-phenyl-9-diethylaminoethylimidazo[1,2-a]benzimidazole dinitrate in ethanol-prednisolone damage to gastric mucosa - M. V. Chernikov; M. A. Oganova; S. A. Kalashnikova; L. V. Polyakova; N. A. Khromova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2020)
Nowadays, the search for new effective and safe medicines for the treatment of acid-dependent gastrointestinal diseases remains an urgent problem of modern pharmacology.The aim of this study was an experimentally study of the anti-ulcer activity of 2-phenyl-9-diethylaminoethylimidazo[1,2-a]benzimidazole dinitrate on the model of damage to the gastric mucosa caused by the administration of 80% ethanol and prednisolone combination (20 mg/kg).Materials and methods. To simulate the damage to the gastric mucosa, the experimental animals (white male Wistar rats) were administrated with prednisone at the rate of 20 mg/kg and 80% ethyl alcohol at the dose of 0.6 ml/100 g of the animal body weight. Prednisolone was dissolved in 80% alcohol. Antisecretory antiulcer agents actively used in clinical practice, were selected as reference drugs: ranitidine (30 mg/kg, 10 mg/kg and 3 mg/kg) and omeprazole (3 mg/kg, 1 mg/kg and 0.3 mg/kg). The studied compound was used at the doses of 30 mg/kg, 10 mg/kg and 3 mg/kg. All the substances under study were administered intragastrically with the use of an atraumatic probe. Results. It has been established that the benzimidazole derivative in the studied doses contributes to a dose-dependent reliable reduction in the area and depth of ulcerative lesions of the gastric mucosae relative to the control and reference drugs (ranitidine and omeprazole). In addition, in the maximum studied dose (30 mg/kg), the proportion of the animals with ulcerative lesions significantly decreases by more than 2 times. The calculated ED50 values for the benzimidazole derivative and ranitidine were 5.09 mg/kg and 38.23 mg/kg, respectively.Conclusion. The obtained experimental data indicate that the benzimidazole derivative has a pronounced dose-dependent antiulcer effect on the model of ethanol-prednisolone erosive-ulcerous defects of the rats' gastric mucosae, which is superior to the effects of the reference preparations. It makes its further study promising.